LEGALITAS BITCOIN SEBAGAI ASET INVESTASI DALAM PERATURAN BAPPEBTI NOMOR 5 TAHUN 2019 PERSPEKTIF SIYASAH SYAR’IYYAH - Dahnial; Kurniati, Kurniati (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The aim of this research is to understand the regulations of bitcoin as an investment asset according to Bappebti Regulation No. 5 of 2019 and to examine the benefits of bitcoin as an investment asset from the perspective of siyasah syar’iyyah. This study employs a qualitative approach with a literature review. After discussing bitcoin's legality as an investment asset from the siyasah syar’iyyah perspective, the researcher concludes that bitcoin is acknowledged as a crypto asset or commodity that meets Bappebti's requirements for investment and is authorized by the state through Bappebti Regulation No. 5 of 2019 on the Technical Provisions for Crypto Asset Physical Market Implementation on the Futures Exchange. The examination of the benefits of bitcoin as an investment asset from the siyasah syar’iyyah perspective includes analyzing its strengths, weaknesses, opportunities, and threats. Based on this analysis, the researcher concludes that crypto assets are permissible as long as they have a clear underlying purpose and benefits, contributing positively to the welfare of society and not used as speculative tools that could harm others.